Where the Aryl Hydrocarbon Receptor Meets the microRNAs: Literature Review of the Last 10 Years - Disner, Geonildo Rodrigo; Lopes-Ferreira, Monica; Lima, Carla (Frontiers in Molecular Biosciences, 2021)
The aryl hydrocarbon receptor (AhR) is an environmentally responsive ligand-activated transcription factor, identified in the ‘70s for its toxic responses to halogenated polycyclic aromatic hydrocarbons, such as dioxin. Recently, AhR has been recognized as engaged in multiple physiological processes in health and diseases, particularly in the immune system, inflammatory response, tumorigenesis, and cellular differentiation by epigenetic mechanisms involving miRNAs. However, there is still scarce information about AhR-dependent miRNA regulation and miRNA-mediated epigenetic control in pathologies and therapies. In this review, we explore the mutual regulation of AhR and miRNA over the last decade of studies since many miRNAs have dioxin response elements (DRE) in their 3’ UTR, as well as AhR might contain binding sites of miRNAs. TCDD is the most used ligand to investigate the impact of AhR activation, and the immune system is one of the most sensitive of its targets. An association between TCDD-activated AhR and epigenetic mechanisms like post-transcriptional regulation by miRNAs, DNA methylation, or histone modification has already been confirmed. Besides, several studies have shown that AhR-induced miR-212/132 cluster suppresses cancers, attenuates autoimmune diseases, and has an anti-inflammatory role in different immune responses by regulating cytokine levels and immune cells. Together the ever-expanding new AhR roles and the miRNA therapeutics are a prominent segment among biopharmaceuticals. Additionally, AhR-activated miRNAs can serve as valuable biomarkers of diseases, notably cancer progression or suppression and chemical exposure. Once AhR-dependent gene expression may hinge on the ligand, cell type, and context singularity, the reviewed outcomes might help contextualize state of the art and support new trends and emerging opportunities in the field.